A participatory approach for developing a geospatial toolkit for mapping the suitability of California’s Multibenefit Land Repurposing Program (MLRP) in support of groundwater sustainability - Nuñez-Bolaño, Yelenka; Flores-Landeros, Humberto; Rodríguez-Flores, José M.; Fernandez-Bou, Angel S.; Medellín-Azuara, Josué; Harmon, Thomas C. (Frontiers in Water, 2025)
Reliance on groundwater during drought cycles is a common cause of overdraft conditions, particularly in regions dominated by irrigated agriculture. Groundwater overdraft is evidenced by declining water table levels, widespread well failure, and land subsidence. Given the severity of these outcomes, natural resource managers are under increasing pressure to create economic and equitable sustainability plans in response to human water demands and climate change impacts. This work describes the development of a novel toolkit (software) designed to support multicriteria decisions centered around restoring groundwater sustainability in overdrafted regions. The toolkit was developed collaboratively with participants in California’s Multibenefit Land Repurposing Program (MLRP), which aims to repurpose irrigated agricultural land to reduce groundwater extraction while providing multiple benefits. The toolkit integrates existing spatial data layers using a Web-based, open-source package (Shiny R) to assess the suitability of land for repurposing. We used fuzzy logic to create six land repurposing suitability indices for (1) enhancing groundwater recharge, (2) minimizing negative impacts to the agricultural economy, (3) increasing renewable energy production, (4) increasing wildlife habitat restoration and conservation, (5) mitigating local flood risk, and (6) reducing environmental health risks in disadvantaged communities. These indices (or subsets) can be combined as weighted averages to create user-specified multibenefit scenarios. The resulting output can be inspected locally to screen prospective land parcels based on their repurposing potential, or holistically to prioritize specific areas in the context of regional land repurposing strategies. We illustrate the development, application, and possible uses of the toolkit in the context of two critically overdrafted groundwater subbasins, Tule and Kaweah, both located in California’s San Joaquin Valley. The methods described are transferable to other overdrafted regions assuming that adequate geospatial data is available. Given its Web-accessibility and user-controlled weighting scheme, the MLRP toolkit can facilitate regional coordination of resource agencies and stakeholders and help to maximize multiple benefits of land repurposing while achieving groundwater sustainability.